UPAYA PENINGKATAN IMUNITAS TUBUH DALAM PENCEGAHAN COVID-19 - Exda Hanung Lidiana; Norman Wijaya Gati; Sri Hartutik (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The specific immune system has the ability to recognize objects that are considered foreign to itself. The first foreign object that appears in the body is immediately recognized by the specific immune system, which will sensitize the immune system. The immune system has three main functions, namely the function of being able to recognize and distinguish various molecular targets and also have a specific response, the ability to distinguish between self-antigens and foreign antigens, and the ability through previous experience of contact with pathogens. foreign substances react faster and faster than the first contact. The method used is the health education method, efforts to increase body immunity in preventing COVID-19 in Jati Village, Jaten District, Karanganyar Regency, and carried out in March 2021. The results of the evaluation after the counseling were that most of the participants understood the problems they were experiencing. There was a change and an increase in the knowledge of the participants from the respondents' knowledge level of good (41%), sufficient (56%) and less (3%) then after counseling there was a change in the level of knowledge from good to (71%) and sufficient knowledge level (29%)